MIĘDZYNARODOWE KOMISJE BADAWCZE W NOWOCZESNYM SYSTEMIE POKOJOWEGO ROZWIĄZYWANIA SPORÓW MIĘDZYNARODOWYCH - Rudnicki, Zbigniew B. (Zeszyty Prawnicze, 2016)
INTERNATIONAL COMMISSIONS OF INQUIRY ON THE MODERN SYSTEM OF PACIFIC SETTLEMENT OF INTERNATIONAL DISPUTES Summary What are the basic characteristics of international inquiry as a separate procedure, distinguishing it from other methods of settlement? In the first place, the agency conducting the inquiry is an international commission usually containing some impartial members of a third party, providing a “neutral” element; occasionally, an equal number of representatives of both parties compose a commission. Secondly, the final effort of the commission, which is a report, has no binding effect. The procedures thus fall into a category of non-obligatory or advisory methods along with negotiations and conciliation. A third characteristic is that the task of the commission is confined to an elucidation of the facts and the issue. If it is authorized to endeavor to effect a settlement either by presenting recommendations in the report or to the parties directly during the course of its work, it no longer remains exclusively a commission of inquiry but becomes instead a commission of inquiry and conciliation. The article discusses the origins of international fact-finding and the most characteristic cases of activities of international commissions of inquiry, established under the Hague Conventions and other instruments adopted by international organizations after the I World War.